2021
DOI: 10.1002/cnr2.1409
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight exposure in infancy decreases risk of sporadic retinoblastoma, extent of intraocular disease

Abstract: Background: Prior ecologic studies suggest that UV exposure through sunlight to the retina might contribute to increased retinoblastoma incidence.Aims: Our study objectives were (1) to examine the relationship between exposure to sunlight during postnatal retinal development (prior to diagnosis of sporadic disease) and the risk of retinoblastoma, and (2) to examine the relationship between sun exposure during postnatal retinal development, and the extent of disease among children with unilateral and bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(60 reference statements)
0
3
0
Order By: Relevance
“… 127 A more recent study showed that infants with higher sunlight exposure had a reduced risk of developing sporadic RB. 128 Together, these studies suggest a relationship between vitamin D and RB, however, further studies are needed to confirm the association.…”
Section: Vitamin Dmentioning
confidence: 90%
“… 127 A more recent study showed that infants with higher sunlight exposure had a reduced risk of developing sporadic RB. 128 Together, these studies suggest a relationship between vitamin D and RB, however, further studies are needed to confirm the association.…”
Section: Vitamin Dmentioning
confidence: 90%
“…The scientific basis of light therapy can be traced back to the late 19th century when researchers revealed that light plays a significant role in regulating various levels of animal life activities, such as gene expression, energy metabolism, cell proliferation, skeletal development, and ontogenesis. 7,9,10 In 1895, the Danish physician Niels R. Finsen discovered that red light helped the healing of skin lesions in patients with smallpox and lupus vulgaris. 11 Subsequently, he used this method to cure nearly a thousand patients, and then paved the way for scientific light therapy, for which he received the Nobel Prize in Medicine in 1903.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is a fat-soluble vitamin recommended for exclusively breastfeeding infants. They can gain it through supplementation or sunlight exposure which produces it from the body [ 5 ]. The human body can generate about 80% of the vitamin D required for the body through sunlight exposure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%